2014
DOI: 10.1016/j.jacc.2014.06.1205
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Diastolic Vortex Ring to Left Ventricular Filling

Abstract: The diastolic vortex is responsible for entering a significant fraction of LV filling volume at no energetic or pressure cost. Thus, intraventricular fluid mechanics are an important determinant of global chamber LV operative stiffness. Reduced stiffness in NIDCM is partially related to enhanced vorticity. Conversely, impaired vortex generation is an unreported mechanism of diastolic dysfunction in HCM and probably other causes of concentric remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 37 publications
5
101
0
Order By: Relevance
“…Vortex ring formation at the tip of the LAVV might play an important role in redirecting the flow toward the aorta. 22 Furthermore, a recent study showed pressure difference, not only between apical and basal level, but also between contralateral segments in healthy volunteers, which possibly influences blood flow pathways. 23 The high percentage of particles in inferior, inferolateral, and anterolateral segments is in line with visually described flow patterns in the LV as reported by Eriksson et al 9 Corrected AVSD Patients Patients with corrected AVSD had a reduced percentage of direct flow but increased delayed ejection flow, resulting in a similar stroke volume as in healthy controls, as was also observed in patients with dilated cardiomyopathy.…”
Section: Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vortex ring formation at the tip of the LAVV might play an important role in redirecting the flow toward the aorta. 22 Furthermore, a recent study showed pressure difference, not only between apical and basal level, but also between contralateral segments in healthy volunteers, which possibly influences blood flow pathways. 23 The high percentage of particles in inferior, inferolateral, and anterolateral segments is in line with visually described flow patterns in the LV as reported by Eriksson et al 9 Corrected AVSD Patients Patients with corrected AVSD had a reduced percentage of direct flow but increased delayed ejection flow, resulting in a similar stroke volume as in healthy controls, as was also observed in patients with dilated cardiomyopathy.…”
Section: Healthy Controlsmentioning
confidence: 99%
“…Next to the lateral inflow, patients presented with an increase of inflow into the apical segments, which may be a result of lateral inflow. Possibly, abnormal formation of the vortex ring, which is suggested to redirect flow toward the aorta, 22 at the tip of the LAVV, in patients allows blood to propagate toward the apex. To further analyze the consequences of these altered intracardiac flow patterns, we divided the inflow into direct flow and retained flow components and observed an increased percentage of particles entering the midlateral segments.…”
Section: Healthy Controlsmentioning
confidence: 99%
“…In the normal heart, a large part of the left ventricular blood volume is actually involved in the vortex formation. Recent in-vivo observations suggest that the vortices that form during left ventricular filling have specific geometries and locations, which could be determinant factors of the diastolic function [42], [165], [114], [118], [166]. Intraventricular vortex flow imaging is becoming increasingly popular in the clinical literature and it is anticipated that accurate measures of the intracardiac vortex hemodynamics might play a key role in the assessment of the cardiac function (Fig.…”
Section: Left Ventricular Vortex Formation and Diastologymentioning
confidence: 99%
“…With this technique, Martínez-Legazpi et al have recently documented that the diastolic vortex is responsible for entering a significant fraction of LV filling volume at no cost to energy or pressure 37. Thus, intraventricular fluid mechanics are an important determinant of global chamber LV operative stiffness.…”
Section: Pathophysiologymentioning
confidence: 99%